THE INFLUENCE OF ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF HOSPITAL EMPLOYEES IN INDONESIA: LITERATURE REVIEW - Yulianti, Yunika Tri; Lailiyah, Syifaul (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: Change in the health sector from various aspects require that every organization carry out a transformation and strategy in responding to it. It is crucial for hospitals to cultivate a favorable organizational culture to effectively contribute to the realization of their vision, purpose, and goals. Organizational culture significantly impacts the performance of individuals inside an organization or employees within a corporation. Purpose: This study aims to investigate the impact of organizational culture on the job performance of hospital employees in Indonesia using literature review. Methods: This literature study uses literature review. The library sources used by Google Scholar, PubMed, and ScienceDirect, using search articles for the last 5 years 2019-2023 produced 18 articles to be reviewed, but only 12 articles had relevant topics. Results: Organizational culture has a favorable impact on hospital employee’s performance. Given that organizational culture is dynamic, a weak organizational culture will impact employee performance. Conclusion: Organizational culture can facilitate the process of health services in hospitals. In hospitals that have a strong organizational culture, it will have an impact on producing good performance in the short, medium, and long term.